International financial reporting standards implementation : a global experience - Nurunnabi, Mohammad (Contributions to international accounting, 2021)
The vast majority of national authorities have made a public commitment supporting a single set of high-quality global accounting standards as of January 13, 2021 requiring or permitting the use of IFRS Standards for domestic, publicly accountable companies and institutions. This includes all member states of the European Union (EU) and the European Economic Area (EEA), in which IFRS Standards are mandatory for all companies whose securities trade in a regulated market. Despite this, there still remains a lack of research on International Financial Reporting Standards (IFRS) implementation and this inaugural volume of Contributions to International Accounting (CIA) aims to address this vital gap, focusing on providing relevant and timely information for local and international policymakers.